Approved and Off-Label Use of Prescribed Psychotropic Medications among Federal Canadian Inmates. (October 2018) - Brown, Gregory P.; Stewart, Lynn A.; Rabinowitz, Terry; Boudreau, Harold; Wright, Angela J.
Objective: To examine psychotropic medication prescription practices in federal Canadian penitentiaries. Method: 468 files were drawn from a purposive sample of thirteen Canadian federal institutions representing the five regions, different security levels, and male and female designated facilities. Information on the names of all psychotropic medications prescribed, indications for use, dosage, frequency, and route of administration was retrieved. Designation of approved or off-label use of medications was determined by consulting: (1) the Health Canada (2016) Drug Product Database, (2) the Canadian Compendium of Pharmaceuticals and Specialties 2016, and (3) the American Hospital Formulary Service Drug Information 2016. Prescription rates were examined by gender, Indigenous ancestry, drug class, institutional infractions, and current offence. Results: 36.2% of prescriptions for psychotropic medication were coded as 'off-label'. Anxiolytic/hypnotics drugs were the psychotropic drugs most commonly used for off-label purposes. There were no differences in the prevalence of approved versus off-label prescriptions based on Indigenous ancestry or gender, and no pattern of elevated off-label prescription practices for offenders involved in institutional misconducts or those sentenced for the most serious crimes. Conclusions: The rates of prescribing 'off-label' psychotropic medication are not elevated relative to other correctional settings or to rates cited in Canadian surveys conducted in the community.